EXPLORING TEACHER’S STRATEGIES IN TEACHING VOCABULARY at GRADE TENTH of SMK SULTAN AGUNG SUMBER - Nia Meliana; Amroh Umaemah; Hendi Hidayat (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2018)
Abstract: Vocabulary is an essential part in learning language. The teacher of SMK Sultan AgungSumber applied the vocabulary strategy in teaching English to make students learn effectively. This study is intended to explore the types, the strengths, and the weaknesses of strategyapplied by the teacher in teaching vocabulary at grade tenth of SMK Sultan AgungSumber.The research method adopted by the researchers is descriptive qualitative. The data are taken from observation and interview with the teacher and 5 students as respondents. Both observation and interview are to explore how the teacher appliesstrategies in teaching vocabulary during the learning process. The result of the study revealed that the strategies applied by the teacher to teach vocabulary includes: 1) comprehending vocabulary in details; 2) memorizing vocabulary in every meeting; 3) dictionary use; and 4) teaching vocabulary by using games. Meanwhile, for the strengths and weaknesses of each strategy, the researcher found that the most effective strategy in teaching vocabulary applied by the teacher is teaching vocabulary by using games. On the other hand, the most weaknesses vocabulary teaching strategy is memorizing vocabulary in every meeting due to the fact thatmemorizing vocabulary around 15-20 words each meeting made them easy to forget thevocabularies that they have memorized. Keywords:Teaching Strategies, Vocabulary